2021
DOI: 10.1016/j.lrr.2021.100251
|View full text |Cite|
|
Sign up to set email alerts
|

Acute myeloid leukemia with hepatic infiltration presenting as obstructive jaundice

Abstract: Highlights Acute myeloid leukemia can present as cholestasis with obstructive jaundice. Extramedullary leukemia infiltration of liver can delay initiation of chemotherapy. Hydroxyurea may be employed as a temporizing measure for effects of hyperleukocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Because emvododstat and desmethyl emvododstat were metabolized exclusively by the liver, it was assumed that the PKs and hepatic effects of emvododstat and desmethyl emvododstat in patients with AML with normal hepatic function would be similar to those in healthy subjects. Although rare, hepatic infiltration and dysfunction have been reported in patients with AML 25 . Underlying liver conditions and co‐administered drugs may impact hepatic safety of emvododstat in patients with AML, which warrants further investigation and simulations with these specific conditions to inform the liver safety of emvododstat in such cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because emvododstat and desmethyl emvododstat were metabolized exclusively by the liver, it was assumed that the PKs and hepatic effects of emvododstat and desmethyl emvododstat in patients with AML with normal hepatic function would be similar to those in healthy subjects. Although rare, hepatic infiltration and dysfunction have been reported in patients with AML 25 . Underlying liver conditions and co‐administered drugs may impact hepatic safety of emvododstat in patients with AML, which warrants further investigation and simulations with these specific conditions to inform the liver safety of emvododstat in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, hepatic infiltration and dysfunction have been reported in patients with AML. 25 Underlying liver conditions and co-administered drugs may impact hepatic safety of emvododstat in patients with AML, which warrants further investigation and simulations with these specific conditions to inform the liver safety of emvododstat in such cases.…”
Section: Articlementioning
confidence: 99%
“…Liver involvement: Though liver involvement as hepatomegaly is lesser than ALL clinically, postmortem studies have demonstrated up to 75% involvement of the liver[ 29 ]. Acute hepatitis may present as conjugated jaundice due to granulocytic sarcoma impeding bile flow or due to myeloid cell infiltration[ 30 ]. Acute liver failure at presentation is rarely reported with pediatric AML posing significant challenges to chemotherapy administration and invariably had poor outcomes in the cases described in the literature[ 31 ].…”
Section: Leukemias In Childrenmentioning
confidence: 99%